Case report: splicing effect of a novel heterozygous variant of the NUS1 gene in a child with epilepsy - Hu, Yan; Huang, Mingwei; Wen, Jialun; Gao, Jian; Long, Weiwei; Shen, Yansheng; Zeng, Qi; Chen, Yan; Zhang, Tian; Liao, Jianxiang; Liu, Qiuli; Li, Nannan; et al. (Frontiers in Genetics, 2023)
NUS1 is responsible for encoding Nogo-B receptor (NgBR), which is a subunit of cis-prenyltransferase. Over 25 variants in NUS1 have been reported, and these variants have been associated with various phenotypes such as congenital glycosylation disorders (CDG) and developmental and epileptic encephalopathy (DEE).Our patient presented with language and motor retardation, epilepsy, and electroencephalogram abnormalities. Upon conducting whole exome sequencing, we discovered a novel and pathogenic variant (chr6:118024873, NM_138459.5: c.791+6T>G) in NUS1, which was shown to cause exon 4 to be skipped, resulting in a loss of 56 amino acids. Our study strongly suggests that this novel variant of NUS1 is responsible for the development of neurological disorders, including epilepsy. It is believed that the truncation of NgBR results in the loss of cis-prenyltransferase activity, which may be the underlying cause of the disease.